TRANSFORMATION OF LENS EPITHELIAL CELLS INTO STEM CELLS FOR REGENERATIVE THERAPY APPLICATIONS IN OCULAR TISSUE - Khadijah, Nurul; Damawati, Esti Utami (Stem Cell Research and Development Center, Universitas Airlangga, 2025)
Visual impairment and blindness remain major global health challenges, driven primarily by cataract, corneal disorders, retinal degeneration, and glaucoma. Although current surgical and pharmacological interventions improve visual outcomes, they do not address the fundamental limitation of irreversible tissue loss. Consequently, regenerative medicine has emerged as a promising approach in ophthalmology, with stem cell–based therapies receiving considerable attention. Among ocular tissues, the lens epithelium has recently been recognized as a potential endogenous source of cells with regenerative capacity. Lens epithelial cells (LECs), which persist throughout life beneath the anterior lens capsule, retain proliferative activity and exhibit notable cellular plasticity. Increasing evidence suggests that LECs can acquire stem cell–like properties under specific biological, molecular, or microenvironmental conditions. This review systematically synthesizes current evidence on the transformation of LECs into stem cell–like or lens progenitor cells and evaluates their potential applications in ocular regenerative therapy. A structured literature search of PubMed and Google Scholar was conducted for English-language studies published between 2020 and 2025, followed by systematic screening and qualitative narrative synthesis. Experimental findings demonstrate that subsets of LECs express pluripotency-associated transcription factors, including SOX2, PAX6, OCT4, and NANOG, and can be induced to form lentoid bodies and lens-like structures in vitro. Lens capsule–based regeneration models and preclinical animal studies further support the capacity of LECs to regenerate lens tissue and partially restore optical function when guided by appropriate molecular cues. Overall, LEC-derived stem cell strategies offer compelling advantages, including reduced immunogenicity, tissue-specific compatibility, and ethical feasibility. Nevertheless, challenges related to controlled reprogramming, safety, and long-term functionality must be addressed to enable successful clinical translation.